2010
DOI: 10.2174/1874192401004010089
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Function and Inflammation in Rheumatoid Arthritis: the Role of Physical Activity

Abstract: Inflammation disturbs biochemical pathways involved in homeostasis of the endothelium. Research has established clear links between inflammatory mediators, particularly C-reactive protein and tumour necrosis factor alpha, endothelial dysfunction, and atherosclerosis. Endothelial dysfunction and atherosclerosis may be subclinical at early stages, and thus the ability to detect them with non-invasive techniques is crucially important, particularly in populations at increased risk for cardiovascular disease, such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 112 publications
1
57
0
1
Order By: Relevance
“…Regular physical activity is also associated with decreased depression [10] and improvements in other disease-related characteristics, such as reduced pain, stiffness and inflammation in this population [2,11,12]. Importantly, research has shown that physical activity is safe for people who have RA [13], despite previous concerns that it may have negative consequences, such as increasing joint erosion [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regular physical activity is also associated with decreased depression [10] and improvements in other disease-related characteristics, such as reduced pain, stiffness and inflammation in this population [2,11,12]. Importantly, research has shown that physical activity is safe for people who have RA [13], despite previous concerns that it may have negative consequences, such as increasing joint erosion [14].…”
Section: Introductionmentioning
confidence: 99%
“…This is of concern given the risk of cardiovascular disease in people who have RA. Promoting physical activity behaviour, with the aim of increasing physical activity participation for this group, is important for improving health outcomes [2,11,12]. Thus, the promotion of physical activity for people who have RA is a key challenge faced by healthcare professionals [18].…”
Section: Introductionmentioning
confidence: 99%
“…AlĂ©m da terapĂȘutica fĂ­sica e farmacolĂłgica, evidĂȘncias cientĂ­ficas tĂȘm demonstrado, ao longo dos anos, os benefĂ­cios da atividade fĂ­sica no tratamento da artrite reumatoide em ambiente clĂ­nico, bem como em ambiente domĂ©stico, com supervisĂŁo profissional 42,43,44 . Apenas 31 pacientes informaram realizar atividades fĂ­sicas regularmente.…”
Section: Representanteunclassified
“…In the short term, intense physical exercise produces a transitory inflammatory response which is reflected in an increase in acute phase reactants and cytokines that is proportional to the amount of exercise and muscle damage. Nevertheless, regular physical activity (training) is associated with a chronic anti-inflammatory response that influences levels of acute phase reactants such as ultra-sensitive CRP and also affects www.intechopen.com lipids and lipoproteins (61)(62)(63)(64). However, Sadepghipour et al in 2010 found no relationship between CRP and physical activity in schoolchildren (65).…”
Section: Cardiovascular Risk Factors and Physical Activitymentioning
confidence: 99%